FLOTATION CIRCUIT PERFORMANCE DETERMINATION USING SIZE BY SIZE RECOVERY €“ CASE OF BULYANHULU GOLD MINE - Maronga, Silvanus J; Ngoroma, Faustine (Tanzania Journal of Engineering and Technology, 2018)
The Bulyanhulu rougher flotation circuit performance has been determined by establishing the performance of individual cells. Direct sampling was done on all the rougher cell input, output and size analysis was performed on the samples with material in each size fraction assayed for copper and gold to determine their recoveries. It was observed that the performance of rougher cell number 3 and 4 was poor compared to other cells especially for finer particles below 53 Î¼m where the recoveries were below 60%. In the last two flotation cells recoveries of both metals was very good (above 90%) in all particle sizes. The comminution circuit designated of 80% passing of 75 Î¼m is still valid since in the last three cells, a good recovery of between 72 and 97% was obtained for both gold and copper in the +53-106 Î¼m size range. Over grinding of the ore to below 53 Î¼m should be minimized since the very fine sizes yield poor recovery of both gold and copper in all cells